Desenvolva os Produtos Notáveis
k)
![(2x - 9 {)}^{2} (2x - 9 {)}^{2}](https://tex.z-dn.net/?f=%282x+-+9+%7B%29%7D%5E%7B2%7D+)
l)
![(a + 4).(a - 4) (a + 4).(a - 4)](https://tex.z-dn.net/?f=%28a+%2B+4%29.%28a+-+4%29)
n)
![(a + 5).(a - 5) (a + 5).(a - 5)](https://tex.z-dn.net/?f=%28a+%2B+5%29.%28a+-+5%29)
m)
![(x + 6).(x - 6) (x + 6).(x - 6)](https://tex.z-dn.net/?f=%28x+%2B+6%29.%28x+-+6%29)
o )
![(x + 7).(x - 7) (x + 7).(x - 7)](https://tex.z-dn.net/?f=%28x+%2B+7%29.%28x+-+7%29)
p)
![(x + 8).(x - 8) (x + 8).(x - 8)](https://tex.z-dn.net/?f=%28x+%2B+8%29.%28x+-+8%29)
q)
![(x + 9).(x - 9) (x + 9).(x - 9)](https://tex.z-dn.net/?f=%28x+%2B+9%29.%28x+-+9%29)
r)
![(x + 10).(x - 10) (x + 10).(x - 10)](https://tex.z-dn.net/?f=%28x+%2B+10%29.%28x+-+10%29)
s)
com cálculo
Soluções para a tarefa
Respondido por
0
k
( 2x - 9)² = [ (2x)² - 2 * 2x * 9 + (9)²] = 4x² - 36x + 81 ***
l
( a + 4 )( a - 4) >>> soma pela diferença
[(a)² - (4)² ] = a² - 16 ***
m
( x + 6 ) ( x - 6 )
[ (x)² - (6)² ] = x² - 36 ****
0
( x + 7 ) ( x - 7 )
[ (x)² - (7)² = x² - 49 ****
p
( x + 8 ) ( x - 8 )
[ (x)² - (8)² ] = x² - 64 ****
q
( x + 9) ( x - 9 )
[ (x)² - (9)² ] = x² - 81 ****
r
( x + 10) ( x - 10 ) =
[ (x)² - ( 10)²] = x² - 100 ***
s
( 3x + 4 ) ( 3x - 4 ) =
[ (3x)² - ( 4 )² ] = 9x² - 16 ***
exalunosp:
obrigada disponha quando precisar
Perguntas interessantes
Psicologia,
11 meses atrás
Matemática,
11 meses atrás
Português,
11 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Biologia,
1 ano atrás